2013
DOI: 10.1016/j.cogpsych.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Multiprocess Framework: Evidence from prospective memory with contextual variability

Abstract: The ability to remember to execute delayed intentions is referred to as prospective memory. Previous theoretical and empirical work has focused on isolating whether a particular prospective memory task is supported either by effortful monitoring processes or by cue-driven spontaneous processes. In the present work, we advance the Dynamic Multiprocess Framework, which contends that both monitoring and spontaneous retrieval may be utilized dynamically to support prospective remembering. To capture the dynamic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
188
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(212 citation statements)
references
References 88 publications
(125 reference statements)
21
188
1
2
Order By: Relevance
“…One debated question is the amount of attention required for successful PM. Previous work suggests that successful PM retrieval is supported by processes such as attentional monitoring (Smith, 2003), cue-driven spontaneous retrieval (Einstein & McDaniel, 2005), or a dynamic combination of both processes (Scullin, McDaniel, & Shelton, 2013). In the present study, we introduce a new method for examining the various processes potentially facilitating PM performance.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…One debated question is the amount of attention required for successful PM. Previous work suggests that successful PM retrieval is supported by processes such as attentional monitoring (Smith, 2003), cue-driven spontaneous retrieval (Einstein & McDaniel, 2005), or a dynamic combination of both processes (Scullin, McDaniel, & Shelton, 2013). In the present study, we introduce a new method for examining the various processes potentially facilitating PM performance.…”
Section: Introductionmentioning
confidence: 93%
“…The MP view predicts monitoring during nonfocal PM tasks, and other types of processing such as spontaneous retrieval, during focal PM tasks. Although much work has advanced our current understanding of the contextual factors and processes that are associated with PM, there is still debate regarding when processes such as monitoring and spontaneous retrieval are utilized (Einstein & McDaniel, 2010;Smith, 2010, also see Scullin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is interesting to note that a recent variant of the multiprocess theory put forward by Scullin et al [24] seems to dovetail with the differential task approach observed in the above-mentioned data. In detail, Scullin et al have suggested that in principle both spontaneous retrieval and controlled processing may be utilized dynamically in one PM task.…”
Section: Major Issues For the Next Decadementioning
confidence: 99%
“…Returning to the prospective memory literature, from this theoretical view most previous studies of event-based prospective memory have used individual stimuli as event cues, such as seeing a word on a screen (e.g., Einstein & McDaniel, 1990;Scullin, McDaniel, & Shelton, 2013) or hearing a recording of a dog bark (Knight, Nicholls, & Titov, 2008). For event cognition theory, these are only a component of events, namely, they are entities within an event.…”
Section: Event Cognitionmentioning
confidence: 99%